Normal Seedlings as A New Parameter for Predicting Cross-Incompatibility Level on Sweetpotato - Febria Cahya Indriani; Sumeru Ashari; Nur Basuki; M. Jusuf (AGRIVITA, Journal of Agricultural Science, 2017)
This research aimed to investigate the incompatibility levels of controlled cross-pollination in sweetpotato, based on normal seedling percentage and their correlation with seed vigour. The controlled cross-pollination in sweetpotato faces issues due to its cross-incompatibility and self-incompatibility characteristics. Currently, the incompatibility level in sweetpotato is investigated based on the fruit set percentage. However, this criterion lacks the ability in accurately predicting the number of new clones. Therefore, it is essential to study new parameters to create a better investigation of incompatibility in sweetpotato. The materials used in this research consisted of eight sweetpotato clones as female and four sweetpotato clones as male parents. Cross-pollinations were done reciprocally. The experiment was conducted at Indonesian Legume and Tuber Crops Research Institute from April to December 2014. The result showed that totally 5,188 times crossing produced about 25% fruit sets and 10% normal seedlings. The use of normal seedlings percentage as a new parameter in evaluating cross-pollination has apparently seemed to be more effective than the fruit sets percentage method because numbers of new clones could be known accurately. This research revealed that the normal seedling could be used as a new parameter in determining the incompatibility level in sweetpotato controlled cross-pollination.